Assessment of peripheral blood DNA methylation signatures as pharmacodynamic and predictive biomarkers during azacitidine therapy in juvenile myelomonocytic leukaemia: results of the EWOG-MESRAT study - Schönung, Maximilian; Rathmann, Silvia; Ramamoorthy, Senthilkumar; Lebrecht, Dirk; Klingebiel, Thomas; Locatelli, Franco; Nysom, Karsten; Rossig, Claudia; Starý, Jan; Zecca, Marco; Patturajan, Meera; Erlacher, Miriam; et al. (British journal of haematology, 2025)
EWOG-MESRAT (European Working Group—Methylation Signatures and Response to Azacitidine Therapy; DRKS00007185) is an investigator-initiated trial that studied EPIC array-based DNA methylation patterns and next generation sequencing (NGS)-based variant allele frequencies (VAFs) of driver mutations in peripheral blood (PB) and bone marrow (BM) of 11 patients with newly diagnosed juvenile myelomonocytic leukaemia (JMML) during therapy with azacitidine. We demonstrate that the pharmacodynamic activity of azacitidine can efficiently be monitored in PB and BM. DNA methylation subgroup classification was linked to clinical response after three cycles of azacitidine and found to be conserved between PB and BM in all patients. In contrast, neither changes in VAFs nor changes in DNA methylation patterns during the course of therapy correlated with therapy outcome among the 11 study patients. This work thus supports the value of DNA methylation subgroup classification from PB samples for response prediction of single-agent azacitidine in patients with JMML.